The audience who knew too much: investigating the role of spontaneous theory of mind on the processing of dramatic irony scenes in film - Cabañas, Cynthia; Senju, Atsushi; Smith, Tim J. (Frontiers in Psychology, 2023)
As in real life, cinema viewers rely on spontaneous theory of mind (SToM) to interpret characters' mental states. Thus, analyzing cinematic structures offers a unique opportunity to examine ecologically valid sociocognitive processes. We conducted a proof-of-concept study (N = 42) to explore how SToM inferences impact film event comprehension in dramatic irony scenes, where knowledge divergence exists between the audience and characters. We hypothesized that spectators would focus more on characters' mental states in such false-belief inducing scenarios compared to scenarios without such disparity. We used six Harold Lloyd silent comedy clips in a narrative comprehension and spontaneous mental state attribution study with a between-subject (Knowledge Manipulation: Installation vs. Control) and within-subject (Phase: Context vs. Exploitation) comparisons. We provided critical information unknown to the characters only to the Installation group and withheld it from the Control group. By comparing differences in participants' descriptions of the clips during the Context phase (varying across groups) and Exploitation phase (same across groups), we evaluated viewers' processing of the same scenes based on their false- or true-belief representations. Our findings indicate that the Installation group used more cognitive mental state words during the Exploitation phase relative to the Context phase, suggesting that exposure to undisclosed critical information enhances the frequency of spontaneous epistemic state inferences and integration into event models of the exploitation. This research advances neurocinematics by highlighting spontaneous sociocognitive processes in event perception and comprehension and provides a novel dramatic irony film corpus and measures for future moment-to-moment SToM processing studies across cognitive-behavioral, physiological, and neural levels.